Gogol's ""Dead Souls"" - Woodward, James B. (Princeton legacy library., 2015)
Alone of the great Russian novels of the nineteenth-century, Dead Souls has remained almost as profound a mystery to critics as it was when it first appeared. James Woodward disputes the traditional view of Gogol's work, contending that it is not a sprawling mass of loosely connected episodes, details, and digressions. His close reading of the text offers a new interpretation by tracing the essential features of Gogol's creative method. Although Dead Souls is a subject of lively debate in almost every respect, no Western scholar has ever before made it the subject of book-length analysis. J.